[RETRACTED] INTEGRATIVE MOTIVATION OF JUNIOR HIGH SCHOOL IN LEARNING ENGLISH IN A GLOBALIZING WORLD - Ogik Adhiarto (Jurnal Penelitian Humaniora, 2013)
The article titled “Integrative Motivation of Junior High School in Learning English in a Globalizing World” (Vol 14, No 2: Agustus 2013, DOI: http://dx.doi.org/10.23917/humaniora.v14i2.864) which had not been published using Open Journal System (OJS) has been retracted by Jurnal Penelitian Humaniora on the grounds of scientific misconduct. A serious issue on plagiarism of the article has been found reaching 85% similarity index to another article authored by Martin Lamb (2004) titled “Integrative motivation in a globalizing world”. In response to our concerns, corresponding author Ogik Adhiarto has been informed that due to the extent and nature of duplication between the articles published in Jurnal Penelitian Humaniora and System, Jurnal Penelitian Humaniora will retract the article and publish a retraction notice.